STUDENTS' DIFFICULTY IN USING PARTS OF SPEECH IN SPOOF TEXT IN STUDENTS OF ENGLISH LANGUAGE EDUCATION PROGRAM - Munthe, Melda Veby Ristella; Sitanggang, Anita; Fukada, Herman; Mobo, Froilan D (Dharmas Education Journal (DE_Journal), 2023)
Grammar is a language to talk about language. Just as one cannot explain how a motor engine functions (or is falling to function) without naming words for its parts and their specific actions, so it is impossible to explore the function of words and the part they play in forming meaningful language without a naming procedure. The purpose of this research is to know the students’ difficulties in using Parts of Speech of a text. This research is a qualitative method with a phenomenological approach. This research was conducted on the first semester student namely 95 students in 2 classess at HKBP Nommensen University Pematangsiantar. The instruments used written test. The results showed the highest one is very good category with 68 students with 71,5% and the fair category with 2 students on the 2,1%. It found no Interjection included. The text used the determiner/ article out of the box of Parts of Speech with 13 words. The dominantly applied by the students in finding the difficulties is stated to the Pronoun, Adjective, and Adverb. The last stated the word of article or determiner into the Adjective.